Competitive Advertising on Brand Search: Traffic Stealing and Customer Selection - Simonov, Andrey; Hill, Shawndra (SSRN Electronic Journal, 2019)
We study the effectiveness of competitive advertising on brand search using a large-scale randomized ad allocation on Bing. Competitors can steal traffic from the focal brand, and they steal an order of magnitude more clicks if the focal brand's link is exogenously removed from the top paid position (6-15% instead of 1-2% of traffic). The traffic stealing is primarily done by the competitor in the top paid link (6-9% of traffic). However, the probability of an immediate conversion on these "stolen'' clicks is low, with 46% of consumers returning to Bing in less than 30 seconds after the click, compared to 3.5-6% for consumers clicking on the focal brand's link. The high probability of quick returns after a click on a competitors' link is due both to negative selection by customers and an incremental increase in the overall number of unsuccessful clicks, with the latter being consistent with both customer confusion and deliberate search. More relevant competitors get more clicks with lower quick-back probability. We discuss the implications of these results for the focal brand's and competitors' advertising strategies, propose an exclusive ad placement mechanism for the platform, and discuss the degree of customer confusion and the social costs imposed by competitive advertising.